PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN RUMAH SAKIT ST CAROLUS JAKARTA PUSAT - Robertus Yanuar H; Nuridin (Jurnal Ekonomi dan Industri, 2022)
Purpose to determine the motivation and work discipline on employee performance of Rumah Sakit St. Carolus Jakarta Pusat. This research is included in the category of causal associative research using a quantitative approach. The population in this study were employees of Rumah Sakit St. Carolus Jakarta Pusat. The sampling method in this research is by simple random sampling technique which is taken randomly. The research method using partially and simultaneous linear regression analysis. The results of the study indicate that partially or simultaneous, motivation and work discipline have a positive and significant effect on employee performance. The coefficient of determination shows that motivation and work discipline contribute 85.9% to employee performance of Rumah Sakit St. Carolus Jakarta Pusat.